Design and Memory: an experience on creative processes in design - Nascimento, Flávio Augusto Araújo; Rezende , Edson José Carpintero (DAT Journal, 2026)
The creative process is constituted in the act of making, influenced by cultural repertoire, academic background, personal history, experimentation, experience, and the individual characteristics of the designer. This article aims to describe and evaluate the experience of the Experimental Group – Design, Affection and Clothing (GEDAI) at the Escola de Design of the Universidade do Estado de Minas Gerais. This is a qualitative study based on a questionnaire applied to students who participated in the 6th edition of GEDAI. The questionnaire, created on the Google Forms platform, was sent via email to 25 students, with 22 responding. The responses were analyzed question by question. The analysis indicates that the experience was perceived as overwhelmingly positive, meaningful, and transformative. The study highlights the importance of memory and the appreciation of personal history, and how these elements can be understood and activated within the creative process.